Study of the impact and relevance of ESAs missions in operational oceanography and climate research and monitoring ... - Bentsen, M.; Bertino, L.; Brusdal, K.; Drange, H.; Evensen, G.; Furevik, T.; Johannessen, J.A.; Lisæter, K.A.; Lygre, K.; Natvik, L.J.; Sagen, H.; Sandø, A.B. (Zenodo, 2003)
The main focus of this study contract is to assess and quantify the relative impact of different Earth Observation data types for climate research and monitoring and for operational ocean prediction systems. The impact has been examined in light of availability of satellite observations of physical oceanographic variables, sea ice variables and marine ecosystem variables. Data from exising satellites including ERS–1 and ERS–2, TOPEX/POSEIDON, NOAA TIROS, DMSP and SeaSTAR has been used. In addition data from Envisat and JASON–1 has been explored, while the impact of Cryosat, SMOS and GOCE has been undertaken using simulated data. ... : NERSC Technical Report no. 233. Funded by the European Space Agency under Contract. no. 14992/01/NL/MM ...